Evaluation of Some Immunological Markers in the Rheumatoid Arthritis Patients - A. Chiad, Ihsan; S.Yossef, Hanaa; A. Al-Saidi, Muntadher; A. Abbas, Mohammed (Iraqi Journal of Science, 2023)
Rheumatoid arthritis (RA) is a chronic inflammatory polyarthritic disease associated with remissions and exacerbations and characteristic genetic, clinical, pathological, and immunological features. The present study was designed to evaluate some immunological parameters of some Iraqi patients with RA. The study was carried out on 75 Iraqi RA patients who were referred to the consultantand which divided into 59 female and 16 male, treated and non-treated. The diagnosis of those patients has been performed under supervision of a specialist physician in rheumatology. Enzyme linked immunosorbent assay (ELISA) technique has been applied for the detection of anti-cyclic citrullinated peptide antibodies (anti-CCP) and (Interleukin-1α (IL-1α). The study revealed that the mean age for RA patients was (46.16±1.24) years with age range (20-67) years. The results of (anti-CCP) antibody showed significant increase in non-treated patients 86.67% (P<0.01) than Methotrexate (MTX) 70.0%, Etanercept(ETN) 53.33% treatment, also in MTX treated patients was significant increased than in ETN treatment while the mean of (IL-1α) was significant increase in non-treated patients 24.57±3.73 pg/ml than in MTX treated patients 13.54±1.16 pg/ml, ETN treated patients 13.06±0.83 pg/ml and healthy control 13.69±1.61 pg/ml. .